PENGARUH PENERAPAN TQM DAN TINGKAT FORMALITAS EVALUASI KINERJA TERHADAP PRODUKTIVITAS KARYAWAN - Lumangkun, Jeane Beatrix; Mildawati, Titik (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
The purpose of this research is to test the influence the total quality management and the formality level ofperformance evaluation partially to the productivity performance of the employees. This research is quantitativeresearch which is done by using statistic method conclusive research and the sample collection technique is doneby using probability sampling. The data is the primary data in the form of questionnaires and the samples are 75employees of PT Barata Indonesia (Persero). The analysis technique is carried out by using multiple regressionanalysis. Based on the result of model feasibility test, it has been found that independent variables: the totalquality management and the formality level of performance evaluation has significant influence to theproductivity of performance of the employees. Based on the result of the t test, it has been found that the totalquality management variable has significant and positive influence to the employees. It indicates that when thetotal quality management in the company is getting better, it can increase the productivity of performance of theemployees. The formality level of performance evaluation has significant and positive influence to the employees.It indicates that the presence of the evaluation which has been done by the company, the performance of theemployees can be known by the company in order to support their operationalKeywords: Total Quality Management, formality level of performance evaluation, Productivity of theEmployees